Horizontal transfer and promotion: New evidence and an interpretation from the perspective of task-specific human capital - Masaru Sasaki; Katsuya Takii; Junmin Wan (Institute for the Study of Labor (IZA), 2012)
This paper provides new evidence about horizontal transfer and promotion using the largest available personnel panel data in Japan and interprets them from the perspective of task-specific human capital. We find that firms synchronize their employees' promotion and horizontal transfers. Then, we show theoretically that task-specific human capital can naturally generate such synchronization. We also find that the directors in an accounting department have the highest probability of being promoted to become board members, while those in a research department have the lowest. This suggests that top managers need a balanced skill set, in which allocative skill is relatively important.
urn:nbn:de:101:1-2012080812292
Keywords: J62; M51; 330; rotation; promotion; task-specific human capital; Erwerbsverlauf; Job Enlargement; Humankapital; Anforderungsprofil; Japan